IMPROVED INTERACTION IN BIOLOGY LEARNING USING "MUTASI VER 1.1" APPLICATION - Yusuf Rizal Libario; Kaspul Kaspul; Muhammad Arsyad (ATRIUM PENDIDIKAN BIOLOGI, 2022)
The learning process in the classroom will work well with the active participation of students in the activities in it, which can increase interest and motivation and deepen understanding of ongoing learning, especially in this digital era. Most student learning activities cannot be separated from what is called a smartphone or device. many learning resources that can be accessed by students, one of which is the "Mutasi ver 1.1" application for android. Mutation application ver 1.1 is an Android-based product that can be developed as a learning medium for students while mutation is an abstract 12th grade Biology Concept and tends to be difficult for students so it is interesting to develop. This development research aims to provide an overview of the validity and practicality of the learning process facilities for the Mutation Application ver 1.1. This development research uses a 4D model but only reaches the Development stage. The results of the development of the Mutation ver 1.1 application show that the application is very effective with a value of 94.80% and practical with a value of 85.27% as a learning process for the concept of Mutation for class XII.